Heidegger, intérprete de San Agustín: el tiempo, nuevas fuentes para la recepción heideggeriana de las Confesiones de San Agustín - Corti, C. Agustín (Revista de Filosofía, 2007)
Based on new textual resources, the article reconstructs and analyses St. Augustine’s interpretation of time made by Heidegger. Two moments are to be distinguished: Whereas the first one is basically critical and epitomizes the Augustinian analysis as an analysis of “vulgar time”, the second one reconsiders this judgement. This result is more accurate but also more condescendential with Heidegger’s own approach on time. However, it distorts some Augustinian concepts, which are reviewed in detail.